DEFINITION OF COMPLEX FUNCTIONS AND CALCULATION OF THEIR DERIVATIVES USING SIMPLE METHODS - Rafikov Fakhriddin Kahakhorovich (International Journal on Integrated Education, 2023)
Two function yi đ index , difference , multiplication and of the ratio derivative . let's say and functions given in being _ at the point and to derivatives have let it be Derivative to the definition